Determinants Effectiveness of Information Technology Governance and IT: Performance in Higher Education Institution (HEI): A Conceptual Framework. - Anwar, Fattah; Hoga, Saragih; Resad, Setyadi (2021)
The purpose of this article is to build a conceptual framework based on literature review that will be tested in future research related to Information Technology Governance (ITG). The results of the literature review allow for the construction of hypotheses into a conceptual framework. Furthermore, the study identifies mechanism that contribute to effectiveness IT governance based on past literatures, on this domain assesses mechanism ITG the influence between information technology performance and effectiveness Information technology governance .The conceptual framework will be tested among higher Education Institution (HEI) users for future research in Indonesia.